POLA KEMITRAAN KOPERASI SEJAHTERA ABADI DALAM MENINGKATKAN KEUNTUNGAN PETANI CABAI - Rudiyanto, Achmad Afif (JEJAK: Jurnal Ekonomi dan Kebijakan, 2014)
This study aims to investigate the implementation of cooperative partnerships Sejahtera Abadi and to determine whether the pattern of cooperative partnerships Sejahtera Abadi impact on the level of benefits that follow partnership chili farmers compa-red to non-partner farmers. The method of collecting data using interviews, observations and questionnaires. Methods of data analysis using the analysis of the advantages of farming and quantitative analysis with different test or independent sample t-test. Based on the survey results revealed that (1) The mechanism of cooperative partnership Sejahtera Abadi which begins with registration chili farmer group members in the cooperative. Before planting the farmers and cooperative partnership cooperati-on through a letter whose contents bahwasannya employment agreement both parties agreed to the binding of the procurement and selling large red chilli (Casium annum var. Grossum cultivars Violin) with specifications that have been determined by PT. Heinz ABC Indonesia. Cooperatives also opened cooperation with investors inputs suppliers to meet the needs of fertilizers, pesticides and pharmaceuticals farmers partners. The payment process by cooperative farmers do every week after the item is received by the system-dated check or wire transfer. (2) The cooperative partnership Sejahtera Abadi impact on partners chili farmer returns. This is shown by the results significantly different test results show the value of t count> t-table which means rejecting the 0.000 probability that showed a significant difference. The results showed that the higher the income of farmers partners compared with non-partner farmers. Suggestions that can give authors are: (1) should the farmers to form farmer groups in order to register as a cooperative partner that can be sold at a higher price. (2) It should give priority to the quality of partner farmers harvest so in accordance with the specifications that are expected by the factory. This will impact on the confidence of the cooperative factories which became partners that will be able to provide a higher price.Â Penelitian ini bertujuan untuk mengetahui pelaksanaan kemitraan Koperasi Sejahtera Abadi dan untuk mengetahui apakah pola hubungan kemitraan Koperasi Sejahtera Abadi berdampak pada tingkat keuntungan petani cabai yang mengikuti kemi-traan dibandingkan dengan petani non mitra. Metode analisis data menggunakan analisis keuntungan usaha tani dan analisis kuantitatif dengan uji beda atau independent sample t-test. Hasilnya Mekanisme pelaksanaan kemitraan Koperasi Sejahtera Abadi diawali dengan pendaftaran anggota kelompok tani cabai di Koperasi. Sebelum masa tanam pihak petani dan koperasi melakukan kerjasama kemitraan melalui surat perjanjian kerja yang isinya bahwasannya kedua belah pihak sepakat untuk pengikatan pengadaan jual beli cabai merah besar dengan spesifikasi yang telah ditentukan oleh PT. Heinz ABC Indonesia. Koperasi juga membuka kerjasama dengan investor pemasok Saprodi untuk memenuhi kebutuhan pupuk, pestisida dan obat-obatan para petani mitra. Proses pembayaran oleh Koperasi kepada petani dilakukan setiap minggu setelah barang dit-erima dengan sistem cek mundur atau transfer. (2) Adanya pola kemitraan Koperasi Sejahtera Abadi berdampak pada tingkat keuntungan petani cabai mitra. Hal ini ditunjukkan dengan hasil hasil uji beda signifikan menunjukan nilai t-hitung > t-tabel yang berarti menolak H_0 dengan probabilitas 0.000 yang menunjukan adanya perbedaan yang signifikan. Hasil penelitian menunjukan bahwa pendapatan petani mitra lebih tinggi dibandingkan dengan petani non mitra.